Diversity of Echinoderms on the Coast of Kuala Langsa - Tasya, Jihan Nabila; Indriaty, Indriaty; Jayanthi, Sri (Universitas Sultan Ageng Tirtayasa, 2025)
Kuala Langsa is one of the coastal areas in Aceh known for its high biodiversity, including animals from the phylum Echinodermata. This study aims to identify Echinodermata species and analyze their populations about the physical and chemical environmental factors of the coastal waters. The research was conducted using a quantitative descriptive method in December 2024 along the coast of Kuala Langsa, Langsa City, with sampling carried out at three transects during low tide. The results showed that five species of Echinodermata from three classes were found. The diversity index was 2.190, indicating a moderate category; the evenness index was 0.830, classified as stable; and the dominance index was 0.358, indicating a low level of dominance. The highest abundance was recorded for Holothuria scabra, while Astropecten cingulatus had the lowest abundance and frequency of occurrence (66.7%). The other four species had a frequency of 100%. The highest similarity index (1) was found between Station II and Station III, while the lowest (0.88) was found between Station I and II and between Station I and Station III. Environmental parameters at the study site showed a temperature range of 29–33°C, pH ranging from 7.2 to 8.5, and salinity ranging from 20–27%. These findings provide important baseline data to support future biodiversity monitoring and highlight the ecological significance of the Kuala Langsa coastal ecosystem.